Forms and Functions of Indonesian-English Code Switching: A Case Study of Elites in Makassar City - Wa Ode Hanafiah (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
The phenomenon of code switching is one of the many social contexts that can help any interaction with the transition from one language to another. The aims of this research are to find out the general patterns of linguistic configuration and socio-pragmatic functions of Indonesian-English code switching. This research used descriptive qualitative and quantitative and the data were collected from 40 elites of different professions in four different types of interactions; seminars, meetings, dialogues on TV, and chitchats employing a direct observation technique including recording and jotting down, and questionnaires. The result of this research is demonstrated that code switching is a crucial phenomenon for a multilingual society. It plays a significant role in governing the social interaction of the community because it has a very wide spectrum of socio-pragmatic implication which significantly contribute to the lives of man whether as an individual being or as a social one